SKRINNING RESEP INTERAKSI OBAT PASIEN DIABETES MELITUS DAN GAGAL GINJAL PERIODE OKTOBER S.D DESEMBER 2023 DI RUMAH SAKIT RASYIDA MEDAN - Rambe, Octia Rambe Octia; Br Sembiring, Novitaria (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Prescription screening is a critical phase in pharmaceutical services conducted bypharmacists and pharmaceutical technical personnel upon receiving aprescription from a patient. This study specifically aims to eval_uate the outcomesof prescription screening based on administrative and pharmaceutical conformityanalysis at Rasyida Hospital, Medan. The research method employed is adescriptive cross-sectional approach with a retrospective design, collecting datafrom the period of October to December 2023. The study reveals thatadministrative eval_uations in prescription screening include several essentialelements such as the patient's name, age/date of birth, address, body weight,the prescribing doctor's name and registration number (SIP), hospital address,doctor’s initials, practice phone number, and the prescription date. On the otherhand, pharmaceutical review focuses on elements such as the name of themedication. With the rising morbidity rate and increased medication use inhospitals, addressing drug-related problems—particularly those stemming frominappropriate medication use—has become more urgent. Prescriptionassessment plays a key role in preventing such issues. This study aims toidentify the elements with the highest level of incompleteness or prescribingerrors. Incomplete prescriptions are a major trigger for medication errors,making prescription screening by pharmacists across healthcare facilities—suchas hospitals, community health centers, and pharmacies—a critical practice.Screening encompasses both administrative and pharmaceutical aspects,highlighting the essential role of pharmacists in mitigating potential health risksfor patients.